Kampanye Kebersihan Lingkungan Melalui Program Kerja Bakti Membangun Desa Blang Krueng, Kecamatan Baitussalam, Aceh Besar - Munir, Afdalul; Nurhayati, Nurhayati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This article aims to raise public awareness in maintaining a clean environment. Environmental cleanliness also plays a very important role in efforts to eradicate Covid-19, because without cleanliness and attention to the environment, this pandemic will never end. This community service-based research was conducted in Blang Krueng Village, Kec. Baitussalam, Aceh Besar uses a Participatory Action Research (PAR) approach. The results of the study show that the awareness of the local community to maintain cleanliness and environmental sustainability still needs to be improved, especially related to the processing of waste and household waste.